An Investigation on the Influences of Construction Schemes on Backfilling the River-Crossing Section of a Utility Tunnel - Jin-Kun Huang; Zhao-Xiang Lu; Wan-Yun Yin; Ren-Cai Jin; Yuan-Di Qian; Si-Dong Shen; Lei Wang (Advances in Materials Science and Engineering)
The backfill construction of a utility tunnel is as important as its main structure construction. While the existing research on utility tunnels focuses on the construction of the main structure, rare attention has been paid to the backfill construction. In this paper, with a practical comprehensive utility tunnel project as the background, a variety of different backfill construction schemes were designed, and the corresponding numerical simulations were performed with the finite element analysis software Midas. The influence of different backfill construction schemes on the side wall, roof, and floor of the utility tunnel was systematically studied and analyzed, and the displacement and stress variation curves in the process of utility tunnel backfill were obtained. Based on the simulation results and the actual engineering situation, the optimal schemes for utility tunnel backfill construction were determined. The results show that the displacement of the side wall of the utility tunnel increased first and then decreased with increasing backfill soil in the unilateral backfill mode, and there was little displacement in the bilateral backfill mode. The shear stress of the side wall of the utility tunnel in both the unilateral and bilateral backfill modes gradually increased with the backfill process. Within the region 1 m above the roof of the utility tunnel, backfill modes had no effect on the final stress and displacement values, but the layering method made a difference. Accordingly, bilateral backfill mode is suggested for the region below the roof of the utility tunnel, while in the case of region 1 m above the roof, backfilling is recommended to be layered according to height rather than position.